Spatial distribution of mangrove species and their association with the substrate sediment types, estuarine sector Térraba-Sierpe National Wetlands, Costa Rica - Barrantes Leiva, Raquel Marcela (Universidad de Costa Rica, 2015)
This research describes the floristic composition and spatial distribution of the main mangroves species and other associated flora present in the estuarine sector of Térraba-Sierpe National Wetland, Costa Rican Pacific. Field survey consists of 1 127 points and 77 sampling points of 60x10m. Results of composition, structure and distribution of mangrove in HNTS exhibits a pattern or species zonation. We found variation from the coast to mainland and from the fringe or estuaries to the interior tidal flats. The species Rhizophora racemosa and Pelliciera rhizophorae showed greater spatial and continuous distribution, with the highest values of abundance (45.44% and 39.92% respectively), frequency (88.31% and 74.03%) and mangrove area (7 670.73ha and 5 824.94ha). The mangrove fern, Acrostichum aureum, was the third most important species, meanwhile, Avicennia spp., Rhizophora mangle y Laguncularia racemosa showed a segregated distribution or a tendency to local conglomeration, Talipariti tiliaceum var. pernambucense, Mora oleifera y Conocarpus erectus were found in very localized areas and other species were considered companions with low contribution to the total coverage. The dependence was confirmed between the presence of mangrove species and sediment type substrate. The species Avicennia spp. and L. racemosa tend to be distributed in sandy substrates more easily than the other species whose distribution is more homogeneous on muddy substrates.